Bartleby's remains: Originality, language, event. (18th October 2019) - Stables, Wayne
Abstract: Taking issue with those readings of Melville's tale that are caught between the need to account for Bartleby and the need to account for the impossibility of the account, this article draws attention to the diverse ways in which 'Bartleby, the Scrivener' harbours a theory of transmission which troubles the function and promise of theory as such. It revisits some of the most influential interpretations of the text before turning to Foucault's 'Thought of the outside' and Derrida's late essay, 'A certain impossible possibility of saying the event'. The nub of the argument is that in the current critical climate, which often seems bent on effecting the most economic relation between textual phenomena and normative orders of historical, cultural or social significance, the most pressing injunction is less to render Bartleby, or his famous 'formula', readable than to show how Melville's text preserves the radical originality of an event, giving us to think that which precedes every measure of equivalence and exceeds the equilibrium of exchange: what remains of language when it has been purged of sense.